Determinants of male involvement in maternal and child health services in sub-Saharan Africa: a review - Ditekemena John; Koole Olivier; Engmann Cyril; Matendo Richard; Tshefu Antoinette; Ryder Robert; Colebunders Robert (BMC, 2012)
Abstract Introduction Male participation is a crucial component in the optimization of Maternal and Child Health (MCH) services. This is especially so where prevention strategies to decrease Mother-to-Child Transmission (MTCT) of Human Immunodeficiency Virus (HIV) are sought. This study aims to identify determinants of male partners' involvement in MCH activities, focusing specifically on HIV prevention of maternal to child transmission (PMTCT) in sub-Saharan Africa. Methods Literature review was conducted using the following data bases: Pubmed/MEDLINE; CINAHL; EMBASE; COCHRANE; Psych INFORMATION and the websites of the International AIDS Society (IAS), the International AIDS Conference and the International Conference on AIDS in Africa (ICASA) 2011. Results We included 34 studies in this review, which reported on male participation in MCH and PMTCT services. The majority of studies defined male participation as male involvement solely during antenatal HIV testing. Other studies defined male involvement as any male participation in HIV couple counseling. We identified three main determinants for male participation in PMTCT services: 1) Socio-demographic factors such as level of education, income status; 2) health services related factors such as opening hours of services, behavior of health providers and the lack of space to accommodate male partners; and 3) Sociologic factors such as beliefs, attitudes and communication between men and women. Conclusion There are many challenges to increase male involvement/participation in PMTCT services. So far, few interventions addressing these challenges have been evaluated and reported. It is clear however that improvement of antenatal care services by making them more male friendly, and health education campaigns to change beliefs and attitudes of men are absolutely needed.